Extract of Stellerachamaejasme L(ESC) inhibits growth and metastasis of human hepatocellular carcinoma via regulating microRNA expression - Xiaoni Liu; Shuang Wang; Jianji Xu; Buxin Kou; Dexi Chen; Yajie Wang; Xiaoxin Zhu (BMC, 2018)
Abstract Background MicroRNAs(miRNAs)are involved in the initiation and progression of hepatocellular carcinoma. ESC, an extract of Stellerachamaejasme L, had been confirmed as a potential anti-tumor extract of Traditional Chinese Medicine. In light of the important role of miRNAs in hepatocellular carcinoma, we questioned whether the inhibitory effects of ESC on hepatocellular carcinoma (HCC) were associated with miRNAs. Methods The proliferation inhibition of ESC on HCC cells was measured with MTT assay. The migration inhibition of ESC on HCC cells was measured with transwell assay. The influences of ESC on growth and metastasis inhibition were evaluated with xenograft tumor model of HCC. Protein expressions were measured with western blot and immunofluorescence methods and miRNA profiles were detected with miRNA array. Differential miRNA and target mRNAs were verified with real-time PCR. Results The results showed that ESC could inhibit proliferation and epithelial mesenchymal transition (EMT) in HCC cells in vitro and tumor growth and metastasis in xenograft models in vivo. miRNA array results showed that 69 differential miRNAs in total of 429 ones were obtained in MHCC97H cells treated by ESC. hsa-miR-107, hsa-miR-638, hsa-miR-106b-5p were selected to be validated with real-time PCR method in HepG2 and MHCC97H cells. Expressions of hsa-miR-107 and hsa-miR-638 increased obviously in HCC cells treated by ESC. Target genes of three miRNAs were also validated with real-time PCR. Interestingly, only target genes of hsa-miR-107 changed greatly. ESC downregulated the MCL1, SALL4 and BCL2 gene expressions significantly but did not influence the expression of CACNA2D1. Conclusion The findings suggested ESC regressed growth and metastasis of human hepatocellular carcinoma via regulating microRNAs expression and their corresponding target genes.